1990
DOI: 10.1037/0022-3514.58.5.864
|View full text |Cite
|
Sign up to set email alerts
|

Conflict over emotional expression: Psychological and physical correlates.

Abstract: This study addresses the construct of conflict or ambivalence over emotional expression. Ambivalence is seen as an important mediator in the link between emotional styles and psychological and physical well-being. Using the "personal striving" framework, a questionnaire measure of ambivalent emotional strivings (AEQ) was designed. In Study 1,292 Ss completed this measure along with questionnaire measures of expressiveness, social desirability, and intense ambivalence. Women scored significantly higher than men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
599
8
33

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 576 publications
(663 citation statements)
references
References 41 publications
(73 reference statements)
23
599
8
33
Order By: Relevance
“…Table 1 summarizes information about the instruments' characteristics. The most frequently reported measure was the Courtauld Emotional Control Scale (Watson & Greer, 1983; n = 32 studies; 56%) followed by the Emotional Approach Coping Scale (Stanton, Kirk, Cameron, & Danoff-Burg, 2000; n = 7 studies; 12%), the Toronto Alexithymia Scale (Bagby, Parker, & Taylor, 1994; n = 6 studies; 11%), the Weinberg Adjustment Inventory -Short Form (Weinberger, 1990; n = 6 studies; 11%), the Stanford Emotional Self-efficacy Scale -Cancer (Giese-Davis et al, 2004; n = 5 studies; 9%), the Cancer ehavior Inventory (Merluzzi, 2001; n = 3 studies; 5%), the Control of Feeling Scale (Benjamin & Friedrich, 1991; n = 3 studies; 5%); the Rationality/Emotional Defensiveness (Spielberger, 1988; n = 3 studies; 5%), the Ambivalence over Emotional Expression Questionnaire (King & Emmons, 1990; n = 2 studies; 4%), the Cognitive Emotion Regulation Questionnaire (Garnefski, Kraaij, & Spinhoven, 2002; n = 2 studies; 4%), and the Emotional Expressiveness Questionnaire (King & Emmons, 1990; n = 2 studies; 4%). A number of relevant scales were used only once: the Berkeley Expressivity Questionnaire (Gross & John, 1995), the COPE (Carver, Scheier, & Weintraub, 1989); the Emotion Self-Disclosure Scale (Snell, Miller, & Beck, 1988), the Marlowe Crowne Social Desirability Scale (Crowne & Marlowe, 1964), and the Ways of Coping Questionnairemodified (Reynolds et al, 2000).…”
Section: Description Of the Instruments Used To Measure Emotion Regulmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes information about the instruments' characteristics. The most frequently reported measure was the Courtauld Emotional Control Scale (Watson & Greer, 1983; n = 32 studies; 56%) followed by the Emotional Approach Coping Scale (Stanton, Kirk, Cameron, & Danoff-Burg, 2000; n = 7 studies; 12%), the Toronto Alexithymia Scale (Bagby, Parker, & Taylor, 1994; n = 6 studies; 11%), the Weinberg Adjustment Inventory -Short Form (Weinberger, 1990; n = 6 studies; 11%), the Stanford Emotional Self-efficacy Scale -Cancer (Giese-Davis et al, 2004; n = 5 studies; 9%), the Cancer ehavior Inventory (Merluzzi, 2001; n = 3 studies; 5%), the Control of Feeling Scale (Benjamin & Friedrich, 1991; n = 3 studies; 5%); the Rationality/Emotional Defensiveness (Spielberger, 1988; n = 3 studies; 5%), the Ambivalence over Emotional Expression Questionnaire (King & Emmons, 1990; n = 2 studies; 4%), the Cognitive Emotion Regulation Questionnaire (Garnefski, Kraaij, & Spinhoven, 2002; n = 2 studies; 4%), and the Emotional Expressiveness Questionnaire (King & Emmons, 1990; n = 2 studies; 4%). A number of relevant scales were used only once: the Berkeley Expressivity Questionnaire (Gross & John, 1995), the COPE (Carver, Scheier, & Weintraub, 1989); the Emotion Self-Disclosure Scale (Snell, Miller, & Beck, 1988), the Marlowe Crowne Social Desirability Scale (Crowne & Marlowe, 1964), and the Ways of Coping Questionnairemodified (Reynolds et al, 2000).…”
Section: Description Of the Instruments Used To Measure Emotion Regulmentioning
confidence: 99%
“…The AEEQ was developed by King and Emmons (1990) to assess ambivalence or worries about expressing emotions. It is a one-dimensional scale and is composed of 28 items (e.g., "I want to express my emotions honestly but I am afraid that it may cause me embarrassment or hurt").…”
Section: The Ambivalence Over Emotional Expression Questionnaire (Aeeq)mentioning
confidence: 99%
See 1 more Smart Citation
“…Below it will be shown that this distinction may be important in relation to hypertension. Type C individuals (Temoshok, 1987), Type D individuals (Denollet et al, 1996) and individuals who have ambivalent feelings towards emotional expression (King and Emmons, 1990) use a deliberate strategy of not expressing emotions in order to please others or to avoid interpersonal conflicts. Type C individuals deliberately suppress negative emotions and are passive in the face of stress (Temoshok, 1987); remarkable similarities can be found with the description of the 'cancer prone personality' (Eysenck, 1995).…”
Section: Conceptual Issuesmentioning
confidence: 99%
“…Even negative affectivity (Watson and Pennebaker, 1989) can be considered to have an important emotional expression component. Consequently, there are several examples of questionnaires measuring emotional expressiveness as a personality characteristic (e.g., Watson and Greer, 1983;Roger and Narajian, 1989;King and Emmons, 1990;Gross and John, 1995).…”
mentioning
confidence: 99%